Formulasi Nanoemulgel Ekstrak Biji Kopi Robusta (Coffea canephora Pierre) Dengan Variasi Gelling Agent Sebagai Antioksidan - reni ariastuti; Raden Roro Karina Pambudi; Ahwan Ahwan (Jurnal Farmasi Indonesia, 2023)
Antioxidants are compounds that are significant in the body's mechanism against free radicals, namely inhibiting oxidative reactions by binding to free radicals or preventing oxidative damage that can lead to oxidative stress conditions. One of the natural ingredients that have antioxidant activity is robusta coffee beans. Robusta coffee beans contain polyphenol compounds have antioxidant activity. Nanoemulgel s a gel preparation that is incorporated in a basic gel and has nano-sized particles. This study aims to 1) determine the stable formula of robusta coffee bean extract nanoemulgel with a variation of gelling agent 2) determine whether the robusta coffee bean extract nanoemulgel has antioxidant activity. The methods used include 1) extraction with maceration 2) nanoemulsions are made using a low-performance technique (magnetic stirrer) and a high performance technique (sonicator) 3) particle size test used dynamic light scattering 4) stability parameters include pH, dispersibility, adhesion, and viscosity 5) antioxidant activity was analyzed using the DPPH method (1,1-diphenyl-2- picrylhydrazyl) 6) statistical analysis used SPSS 21 software using Paired T-test and One Way Anova. The results nanoemulsion particle size of robusta coffee bean extract was 12.3 nm and the polydisperse index was 0.274 nm, the most stable nanoemulgel was formula 3 with varying concentrations of gelling agent (1 gram HPMC: 0.5 gram Carbopol) had an average value of pH 5, average adhesion 1.59 seconds ± 0.01, average dispersion 6.7 cm ± 0.1, and the average viscosity value of 2500 cPs. The formula with the strongest antioxidant activity is formula 1 (0.5- gram carbopol) with an average IC50 value of 10.678 ± 0.0346 ppm.